2004
DOI: 10.1111/j.1445-6664.2003.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy in the rhizosphere and amended soil of Chenopodium murale L.

Abstract: Soil infested with Chenopodium murale and amended with it were investigated to verify their allelopathic effects on seedling emergence and some growth and physiological parameters of five test species, Trifolium alexandrinum, Triticum aestivum, Melilotus indicus, lycopersicum esculentum and Cucumus sativus. The two types of soil exhibited phytotoxic effects on the seedling emergence of the test species. Growth and physiological parameters were significantly inhibited when the soil was amended with a high conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…Earlier, the roots and the residue of C. murale have been reported to release phytotoxic phenolics into the soil affecting the growth and development of other plants (El-Khatib et al 2003;Batish et al 2007). In general, intact roots (Bertin et al 2003) or plant residues upon decomposition (Xuan et al 2005) release secondary metabolites into the rhizosphere soil of a number of plant species.…”
Section: Quantitative and Qualitative Determination Of Phenolic Allelmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, the roots and the residue of C. murale have been reported to release phytotoxic phenolics into the soil affecting the growth and development of other plants (El-Khatib et al 2003;Batish et al 2007). In general, intact roots (Bertin et al 2003) or plant residues upon decomposition (Xuan et al 2005) release secondary metabolites into the rhizosphere soil of a number of plant species.…”
Section: Quantitative and Qualitative Determination Of Phenolic Allelmentioning
confidence: 99%
“…botrytis), pepper (Capsicum annuum L.), wheat, white clover (Trifolium alexandrinum L.), tomato (Lycopersicon esculentum Mill.) and cucumber (Cucumis sativus L.) through its leaf, inflorescence and shoot extracts (Datta and Ghosh 1982;Qasem 1995;El-Khatib et al 2003). However, detailed information about its allelopathic effects, particularly concerning the mechanism of release, amount and nature of allelochemicals involved, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathy is often mediated by secondary metabolites released by the roots (Bais et al 2003). However, the study of plant-plant interactions mediated by roots is aggravated by the complexity of soil as a chemical and biological system that affects the availability of allelochemicals through their retention, transformation and transport (El-Khatib et al 2004a), thus interfering with allelopathic interactions. The bioassays set to elucidate the phytotoxic properties of roots are commonly based on treating target plants with root extracts, but novel tools for sampling root exudates from soil-grown plants (Oburger et al 2013) are promising.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of C. murale are incorporated into the soil during tillage, and water-soluble substances are released after fields are flooded prior planting of lowland rice. El-Khatib et al (2003) reported the allelopathic activities of C. murale rhizosphere soil and soil amended with its leaves. Inderjit (2006) found that activated carbon could not completely eliminate the inhibitory effects of soil amended with high amounts of C. murale leachate, but phytotoxic effects were largely eliminated after addition of Nfertilizers.…”
Section: Introductionmentioning
confidence: 99%